Magnetic properties of high-pressure optical floating-zone grown LaNiO3 single crystals - Dey, Kaustav; Hergett, Waldemar; Telang, Prachi; Mohamed, Mahmoud; Klingeler, Rüdiger (Journal of crystal growth, 2019)
Macroscopic cm-sized single crystals of distorted perovskite LaNiO3 have been grown by means of the optical floating-zone method at oxygen pressures of 40 and 80bar, respectively. Depending on the growth parameters, the crystals feature a transition to long-range antiferromagnetic order as indicated by magnetic susceptibility and specific heat studies or lack of magnetic order. Our findings resemble recent contradictory reports which either imply the presence of unexpected antiferromagnetism (Guo et al., 2018) or the absence of magnetic order (Zhang et al., 2017; Wang et al., 2018). Our data indicate that long-range magnetic order is not intrinsic to LaNiO3.